2017
DOI: 10.3389/fncel.2017.00247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Spontaneous Climbing Fiber Discharge-Evoked Pauses and Output Modulation of Cerebellar Purkinje Cell in Mice

Abstract: Climbing fiber (CF) afferents modulate the frequency and patterns of cerebellar Purkinje cell (PC) simple spike (SS) activity, but its mechanism is unclear. In the present study, we investigated the mechanisms of spontaneous CF discharge-evoked pauses and the output modulation of cerebellar PCs in urethane-anesthetized mice using in vivo whole-cell recording techniques and pharmacological methods. Under voltage-clamp recording conditions, spontaneous CF discharge evoked strong inward currents followed by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…3 C, D ) PCs in 12 months old mice. This reciprocal firing is typical for cerebellar PCs (22, 28) and similar reciprocal response was previously observed for the electrical stimulation of the inferior olive (21, 29). With some delay, the restoration of simple spikes generation was registered as a result of harmaline washout (Fig.…”
Section: Resultssupporting
confidence: 85%
“…3 C, D ) PCs in 12 months old mice. This reciprocal firing is typical for cerebellar PCs (22, 28) and similar reciprocal response was previously observed for the electrical stimulation of the inferior olive (21, 29). With some delay, the restoration of simple spikes generation was registered as a result of harmaline washout (Fig.…”
Section: Resultssupporting
confidence: 85%
“…SK channels have an impact on the setting intrinsic firing frequency [ 90 ] whereas BK channels are involved in the regulation of AP waveform and presumably climbing fiber responses [ 68 91 ]. Recent studies have shown that CF-evoked pause of spontaneous firing and generation of burst firing in PCs require BK channels coupled to Ca 2+ channels [ 92 93 ]. Because SK and BK channels in PCs play a critical role in the regulation of firing behavior, dysfunction of these channels has been implicated in cerebellar disease such as ataxia.…”
Section: Ion Channels and Spiking Activity Of The Cerebellar Pcsmentioning
confidence: 99%
“…In the absence of complex spiking, simple spike firing frequencies increase to exceptionally high levels (Cerminara and Rawson, 2004). SK channels are also responsible for afterhyperpolarisations that follow bursts of action potentials (Ohtsuki et al, 2012), which may underlie the climbing fibre-induced pause and downregulation of simple spikes (Jin et al, 2017). The model of the calcium-activated potassium current used here and taken from Gillies and Willshaw (2006) is one of a number of models for the SK channel, for example, the alternative model used in Griffith et al (2016) based on Chay and Keizer (1983); Xia et al (1998) has a steeper and quicker modulation of the channel by calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The models presented in this study are tuned to match complex spikes recorded in vitro in Davie et al (2008). This example is chosen because it typifies features of the complex spike waveform observed in numerous in vitro studies (Zagha et al, 2008;Zhang et al, 2017;Monsivais et al, 2005;Khaliq and Raman, 2005) and in an in vivo study, Warnaar et al (2015): in vivo studies that give wave form data are less common. These feature, which are broadly stereotypical are 1. the first spike is similar in shape to the simple spike, 2. the first spikelet is smaller in amplitude than subsequent spikelets, 3. spikelets get further apart with increasing current injections or spikelet number.…”
Section: Discussionmentioning
confidence: 99%